(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Ethanolic extract and its n-hexane and chloroform soluble fractions of the leaves of Gardenia coronaria Buch. Ham. were screened for their bio-activities. Preliminary phytochemicals screening of crude extract revealed the presence of glycosides, alkaloids, tannins, saponins, reducing sugars and flavonoids in different extracts. In antibacterial test, maximal zone of inhibition obtained against B. cereus (15.3 mm) and in antifungal test maximal zone found against C. albicans (12.7 mm) by the chloroform extract. The crude extract of the plant exhibited notable anti-inflammatory activity. The antioxidant activity was evaluated by DPPH free radical scavenging method where the scavenging activity was concentration dependent with IC50 values of 5.15μg/ml, 8.75μg/ml and 12.71μg/ml for ethanol, nhexane and chloroform extract, respectively. In the castor oil-induced antidiarrheal assay, the crude extract of the plant significantly increased the latency and total count of defecation. Acetic acid-induced writhing reflex due to analgesia was inhibited by 31.18% (by ethanol), 23.67% (by n-hexane) and 24.73% (by chloroform) at 500 mg/kg body wt. in experimental mice. The extractives at doses from 31.25-500 μg/ml, produced inhibition of amylase activity in a dose dependent manner. Bangladesh Pharmaceutical Journal 20(2): 139-147, 2017